2022
DOI: 10.1002/pc.27148
|View full text |Cite
|
Sign up to set email alerts
|

Tea‐polyphenols mediated interfacial modifier to integrate reinforcement, reprocessability, and shape memory properties into rubber/carbon black composites via coordination bonds

Abstract: Carbon blacks are important fillers to reinforce, functionalize rubber materials and reduce their prices. However, environment-friendly surface modification of carbon blacks is not trivial to conduct, yet challenging to effectively sever broad rubber galleries. Inspired by wet adhesion of mussel, tea polyphenols (TPs) are coated on carbon blacks by vacuum absorption method (i.e., TP@C) and then they are mixed into nitrile butadiene rubber with ZnCl 2 . Specially, Zn 2+ /TP@C coordination interfaces are formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The increase in BRC is mainly attributed to the following factors. On the one hand, the hydroxyl moieties of PSM can interact with the oxygenic groups on the CB surface through the formation of hydrogen and covalent bonds . On the other hand, the polysulfide segments of PSM can cleave into thiyl radicals, which subsequently react with the rubber chains and the polycondensed aromatic on the CB surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in BRC is mainly attributed to the following factors. On the one hand, the hydroxyl moieties of PSM can interact with the oxygenic groups on the CB surface through the formation of hydrogen and covalent bonds . On the other hand, the polysulfide segments of PSM can cleave into thiyl radicals, which subsequently react with the rubber chains and the polycondensed aromatic on the CB surface.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, the hydroxyl moieties of PSM can interact with the oxygenic groups on the CB surface through the formation of hydrogen and covalent bonds. 37 On the other hand, the polysulfide segments of PSM can cleave into thiyl radicals, which subsequently react with the rubber chains and the polycondensed aromatic on the CB surface. Thus, the molecular bridge between the SSBR matrix and CB is established by the dual functions of PSM, thereby making the SSBR adsorb CB more easily (Scheme 2).…”
Section: Thermal Stability and Flame Retardancy Of Psmmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in recent years, there has been a significant increase in interest in the use of tea as an innovative ecological and sustainable ingredient in polymer composites. Previous research shows that teas can be used as antioxidants [4,5], strengthening additives [6] and fillers in polymers [7][8][9]. This variety of applications opens the way to create innovative materials with increased functionality and ecological properties.…”
Section: Introductionmentioning
confidence: 99%
“…At the beginning of the last century, scientists found that adding carbon black (CB) could significantly improve the performance of rubber, 1,2 which promoted the application of carbon black in the rubber industry. [3][4][5][6][7] Nowadays, carbon black has become the most used reinforcing agent in the rubber industry. [8][9][10][11] In 2021, the global production of carbon black was 14.05 million tons, 90% of which was used in the rubber industry.…”
Section: Introductionmentioning
confidence: 99%